2010
DOI: 10.1111/j.1528-1167.2010.02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Densities of glutamatergic and GABAergic presynaptic terminals are altered in experimental cortical dysplasia

Abstract: SUMMARYPurpose: Cortical dysplasia (CD) is a major cause of epilepsy in children and adults, but underlying mechanisms of epileptogenesis in this disorder are poorly understood. We have utilized the irradiated rat model to study an injury-based form of diffuse CD in rats. Prior studies in this model have shown reduced numbers of c-aminobutyric acid (GABA)ergic interneurons and reduced inhibitory synaptic currents in pyramidal cells in CD. We analyzed the number of excitatory and inhibitory presynaptic terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 44 publications
5
30
0
Order By: Relevance
“…As far as the experimental models of epilepsy are concerned, the density of VGAT terminals is reduced in an animal model of cortical dysplasia (Zhou and Roper, 2010), in pre-seizure seizure-sensitive gerbil (Kang et al, 2003) and picrotoxin-induced kindling rat hippocampi (Jiang et al, 2004), although VGAT-IR is unaltered in KA-induced seizures (Sperk et al, 2003). Contrasting evidence exists for changes in VGAT in epileptogenesis induced by pilocarpine.…”
Section: Slc32 Familymentioning
confidence: 99%
“…As far as the experimental models of epilepsy are concerned, the density of VGAT terminals is reduced in an animal model of cortical dysplasia (Zhou and Roper, 2010), in pre-seizure seizure-sensitive gerbil (Kang et al, 2003) and picrotoxin-induced kindling rat hippocampi (Jiang et al, 2004), although VGAT-IR is unaltered in KA-induced seizures (Sperk et al, 2003). Contrasting evidence exists for changes in VGAT in epileptogenesis induced by pilocarpine.…”
Section: Slc32 Familymentioning
confidence: 99%
“…In utero irradiated rats are used as a model of CD (Roper 1998) and most closely resemble type IB CD in humans (Blümcke et al 2011). Our previous histological studies have demonstrated the loss of both interneurons (Deukmedjian et al 2004;Roper et al 1999;Zhou andRoper 2010, 2011) and GABAergic presynaptic terminals (Zhou and Roper 2010) and an increase of the density of glutamatergic terminals in dysplastic cortex (Zhou and Roper 2010). Electrophysiological studies have further confirmed an imbalance between excitatory and inhibitory synaptic inputs to pyramidal neurons (Chen and Roper 2003;Zhu and Roper 2000) and to GABAergic interneurons in irradiated rats with CD (Xiang et al 2006;Zhou et al 2009a;.…”
Section: Dysplastic and Immature Cortex Are More Hyperexcitable And Mmentioning
confidence: 80%
“…Our results suggest that an underlying cause of seizure susceptibility may be related to the malformation of white matter. Fetal irradiation can produce a wide range of structural defects, which include agenesis of the corpus callosum (Roper et al, 1995), reduced numbers of dendrites (Zhou and Roper, 2010), and defective neuronal connections (Naylor et al, 2008). Thus, attenuation of cortical myelin dysplasia might also contribute to the quetiapine's protective effect on seizure susceptibility.…”
Section: Discussionmentioning
confidence: 99%